China-Pakistan Economic Corridor (CPEC): its impact on Pakistan’s economy and society = Koridor Ekonomic China-Pakistan (CPEC): kesan terhadap ekonomic dan sosial di Pakistan - Iftikhar, Zainab; Hossain, Ishtiaq (IIUM Press, 2020)
This paper focuses on the China-Pakistan Economic Corridor (CPEC), a megainitiative of Pakistan and China. The CPEC is important to both Pakistan and China. It is viewed in Pakistan that CPEC is a great opportunity for development of Pakistan. This article examines the impact of CPEC on Pakistan’s economy and society. It highlights the impacts of a number of projects undertaken by CPEC such as infrastructures, Special Economic Zones (SEZ), energy, Gwadar port and social sector projects on Pakistan’s economy and society. This paper adopts a qualitative research method and the analysis made concludes that CPEC has more positive than negative impacts on Pakistani economy and society. In order to draw benefits from CPEC, its proper implementation and functioning is important. ****************************************************************************** Kajian ini membincangkan Koridor Ekonomi China-Pakistan (CPEC) sebagai inisiatif mega antara Pakistan dan China. Projek infrastuktur ini penting untuk keduadua buah negara ini terutamanya dalam memberi peluang kepada pembangunan di Pakistan. Kajian ini juga bertujuan untuk menghuraikan kesan CPEC terhadap sektor ekonomi dan sosial di Pakistan. Ia menekankan kesan projek-projek CPEC seperti dalam infrastruktur, Zon Ekonomi Khas (SEZ), Tenaga, Pelabuhan Gwadar dan projekprojek sektor Sosial untuk ekonomi dan masyarakat Pakistan. Kajian ini telah menggunakan kaedah kualitatif dan analisa dalam mengkaji bahawa pembinaan infrastruktur CPEC mempunyai kesan yang positif berbanding daripada kesan negatif untuk sektor ekonomi dan sosial. Pelaksanaan yang rapi sangat penting untuk mencapai hasil yang memuaskan